2016
DOI: 10.1128/mbio.01282-16
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Vesicle Biosynthesis in Salmonella : Is There More to Gram-Negative Bacteria?

Abstract: Recent research has focused on the biological role of outer membrane vesicles (OMVs), which are derived from the outer membranes (OMs) of Gram-negative bacteria, and their potential exploitation as therapeutics. OMVs have been characterized in many ways and functions. Until recently, research focused on hypothetical and empirical models that addressed the molecular mechanisms of OMV biogenesis, such as vesicles bulging from the OM in various ways. The recently reported study by Elhenawy et al. (mBio 7:e00940-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Their release is a phenomenon observed constitutively in many Gram-negative bacteria, including Salmonella ( Schwechheimer and Kuehn, 2015 ). OMV formation is still poorly understood, even though recent advances have highlighted the importance of the LPS synthesis pathway ( Schwechheimer et al, 2013 ; Bonnington and Kuehn, 2016 ; Elhenawy et al, 2016 ). Environmental conditions such as oxygen or iron availability, growth phase and media composition influence vesicle biogenesis ( Orench-Rivera and Kuehn, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their release is a phenomenon observed constitutively in many Gram-negative bacteria, including Salmonella ( Schwechheimer and Kuehn, 2015 ). OMV formation is still poorly understood, even though recent advances have highlighted the importance of the LPS synthesis pathway ( Schwechheimer et al, 2013 ; Bonnington and Kuehn, 2016 ; Elhenawy et al, 2016 ). Environmental conditions such as oxygen or iron availability, growth phase and media composition influence vesicle biogenesis ( Orench-Rivera and Kuehn, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that adding phospholipids or modified lipopolysaccharides to the bacterial outer membrane could change the curvature of the membrane and increase the number of OMVs released (47). In addition, changing the temperature to affect membrane fluidity and increasing or decreasing LPS acylation level both impact the generation of OMVs (48,49).…”
Section: Formation Of Bacterial Outer Membrane Vesiclesmentioning
confidence: 99%
“…[ 10–12 ] In the previous study, [ 13 ] we constructed outer membrane vesicles (OMVs) derived from Escherichia coli transformed by plasmid DNAs (pDNAs) encoding target gene, showing the unique functions in secreting the targeting protein at the in situ site, making them promising nanoreservoirs and delivery vehicles for protein therapy. [ 14,15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In the previous study, [13] we constructed outer membrane vesicles (OMVs) derived from Escherichia coli transformed by plasmid DNAs (pDNAs) encoding target gene, showing the unique functions in secreting the targeting protein at the in situ site, making them promising nanoreservoirs and delivery vehicles for protein therapy. [14,15] In this study, to construct a simple, efficient, and safe transcutaneous vaccination platform, E. coli (T-E. coli) transformed by pDNAs encoding gp100 and CCL21 genes, respectively, were prepared, from which, the OMVs secreting gp100 (G OMV ) and CCL21 (C OMV ) protein were isolated. G OMV and C OMV were then entrapped into a poly-glycidyl methacrylate-composed porous microneedle (MN) array with conductive properties (named MN-G and MN-C, respectively).…”
mentioning
confidence: 99%